Descending Thoracic Aorta Stenosis Treated by Percutaneous Transluminal Angioplasty and Stenting with Coaxial Sheath Introduction Technique in a Small Child - Ho Anh B; Le Van D; Phan Anh K; Nguyen Thi Bich N; Nguyen Ngoc Minh C; Vo Van K (International Medical Case Reports Journal, 2021)
Binh Ho Anh,1 Duy Le Van,1 Khoa Phan Anh,1 Ngoc Nguyen Thi Bich,1 Chau Nguyen Ngoc Minh,2 Khanh Vo Van1 1Department of Emergency and Interventional Cardiology, Hue Central Hospital, Hue City, Vietnam; 2Pediatric Center, Hue Central Hospital, Hue City, VietnamCorrespondence: Duy Le VanDepartment of Emergency and Interventional Cardiology, Hue Central Hospital, 16 Le Loi Street, Hue City, VietnamEmail lvnduy@gmail.comAbstract: A 10-year-old girl (23 kg) having a medical history of uncontrolled hypertension was presented to our hospital because of acute left heart failure. Transthoracic echocardiography showed stenosis of descending thoracic aorta with a maximum trans-stenotic pressure gradient of 50 mmHg and severe left ventricular systolic dysfunction with an ejection fraction of 20%. She was diagnosed with Takayasu arteritis with a long severe stenosis of segment III of the thoracic aorta. The procedure of percutaneous transluminal angioplasty was performed and helped to reduce the pressure gradient significantly. After a 6-month follow-up, the left ventricular function was unimproved. Hence, aortic angiography was done and revealed the descending thoracic aorta restenosis with a pressure gradient of 46 mmHg. Despite the difficulties of small vascular access and the disease severity, this patient was intervened by cover stent without any complications. The trans-stenotic pressure gradient decreased remarkably to 5 mmHg. The stent implantation should be considered in the severe stenosis of descending thoracic aorta because of its benefit and safety.Keywords: aorta, stenosis, stent, children